Goji Berry (Lycium barbarum): Composition and Health Effects – a Review - Kulczyński Bartosz; Gramza-Michałowska Anna (Polish Journal of Food and Nutrition Sciences)
Goji berries contain many nutrients and bioactive compounds which allowed to classify them as superfruits. A short description of the fruits is presented together with cultivation requirements. The chemical composition of the berries and their health-promoting properties are described later in this literature review. Based on the available data, their potentially beneficial application in dietary prevention of diseases of affluence, such as diabetes, cardiovascular diseases and cancer, is elaborated. We also refer to the safety of Goji consumption in the context of ingredients potentially harmful for human health, allergic reactions and the interactions with other substances.